An Efficient Deep Learning Framework for Revealing the Evolution of Characterization Methods in Nanoscience - Hui-Cong Duan; Long-Xing Lin; Ji-Chun Wang; Tong-Ruo Diao; Sheng-Jie Qiu; Bi-Jun Geng; Jia Shi; Shu Hu; Yang Yang (Nano-Micro Letters)
Highlights A framework combining the citation analysis with topic modeling is designed to construct the knowledge graph of a research field. An extensible tokenizer is designed to improve the universality of the framework, and the performance of topic recognition is superior to that of the traditional method. The detailed evolutionary paths of Raman spectroscopy technology are demonstrated, and the significant publications in the Raman spectroscopy are identified.